2008
DOI: 10.1063/1.2980014
|View full text |Cite
|
Sign up to set email alerts
|

Laser induced plane acoustic wave generation, propagation, and interaction with rigid structures in water

Abstract: Short pulsed laser induced single acoustic wave generation, propagation, interaction with rigid structures, and focusing in water are experimentally and numerically studied. A large area short duration single plane acoustic wave was generated by the thermoelastic interaction of a homogenized nanosecond pulsed laser beam with a liquid-solid interface and propagated at the speed of sound in water. Laser flash schlieren photography was used to visualize the transient interaction of the plane acoustic wave with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The propagation of laser-generated ultrasound from thin metal film deposited on a base material immersed in water is especially of great interest in this study. Propagation of sound waves in the direction perpendicular to the surface of chromium film from the normal laser irradiation was extensively studied by Ko, et al [ 11 , 12 ]. Propagation of sound waves generated in a 0.4-mm-thick stainless steel plate in water for transversal direction was observed by Schlieren imaging [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The propagation of laser-generated ultrasound from thin metal film deposited on a base material immersed in water is especially of great interest in this study. Propagation of sound waves in the direction perpendicular to the surface of chromium film from the normal laser irradiation was extensively studied by Ko, et al [ 11 , 12 ]. Propagation of sound waves generated in a 0.4-mm-thick stainless steel plate in water for transversal direction was observed by Schlieren imaging [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The strongest component of laser-generated ultrasound from PTMF is the bulk wave propagating away from the PTMF which acts as the sound source [ 11 , 12 ]. However, shear wave (or surface acoustic wave) not only propagates within the fused silica plate, but it also generates sound waves in the water with the speed of the shear wave in the propagating direction [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Phase transition in VO 2 , in contrast, is stable up to multiple cycles and transition temperature can be manipulated to different operating temperatures. [20,21] Furthermore, VO 2 can efficiently dissipate the heat generated, which is suitable for brake and clutch applications because it's thermal conductivity increases by 60% with temperature due to transition to metallic phase from insulating phase. [22,23] To confirm our proposed approach, we have performed a thorough nanotribological characterization on VO 2 platelets by FFM and nanoindentation scratch tests.…”
Section: Introductionmentioning
confidence: 99%
“…7). Our previous report [12] showed that the reflected pressure wave from a perfect cylindrical concave surface could be focused to a line R/2 distant from the cylinder wall after the reflection. A similar focusing effect is proposed to explain the local focusing effect of the reflected pressure wave on the curved nozzle wall.…”
Section: Gradual Contraction Wall Channels: Linear Contractionmentioning
confidence: 99%
“…Several numerical simulation studies were carried out to discuss multidimensional laser-induced acoustic wave behavior. Ko et al first reported the time-resolved direct observation of two-or threedimensional laser-induced acoustic wave interaction with submerged solid structures such as single, double, 33 • tilted single block, and concave cylindrical acoustic lens configurations [11,12]. They further demonstrated that these waves can be focused down to a domain of several tens of microns in size and acoustic focusing lens has potential applications to biomaterial processing and characterization.…”
mentioning
confidence: 99%